Analysis of strain and dislocation evolution during MOCVD growth of an AlGaN/GaN power high-electron-mobility transistor structure. (29th May 2019) - Rudinsky, Mikhail; Yakovlev, Eugene; Talalaev, Roman; Novak, Tomas; Kostelnik, Petr; Sik, Jan
Abstract: We present the results of a comprehensive analysis of GaN-on-Si based HEMT epi-wafers grown by metal-organic chemical vapor deposition (MOCVD) in a production-scale reactor. An AlGaN/AlN superlattice was used as the buffer layer. Detailed characterization was combined with process modeling by STREEM-AlGaN software. Comparative analysis of modeling results, characterization data, and in situ curvature measurements allows the study of the evolution of structural properties of the epi-wafer during growth. The initial compressive mean stress in the superlattice gradually decreases during starting period of the growth and then becomes almost constant. The filtering of the dislocations is more effective in the bottom part of the SL, as both experiment and modeling demonstrate large inclination of dislocations in AlGaN layers of the superlattice, while the predicted dislocation density decreases due to annihilation. Proposed buffer layer and growth recipe resulted in final reduction of the dislocation density to ∼2 · 10 8  cm −2 with good structural uniformity over 6″ wafers and a residual bow below 50  μ m.